Autologous transplantation of umbilical cord blood-derived cells in extreme preterm infants: protocol for a safety and feasibility study. Issue 5 (11th May 2020) - Malhotra, Atul; Novak, Iona; Miller, Suzanne Lee; Jenkin, Graham
Abstract : Introduction: Preterm brain injury continues to be an important complication of preterm birth, especially in extremely premature infants. Umbilical cord blood-derived cells (UCBCs) are increasingly being evaluated for their neuroprotective and neuroreparative properties in preclinical and clinical studies. There remains a paucity of information on the feasibility and safety of autologous UCBC transplantation in extremely premature infants. Methods and analysis: A single centre safety and feasibility study in preterm babies born before 28 weeks gestation. Cord blood will be collected after birth and if sufficient blood is obtained, UCB mononuclear cells will be harvested from the cord blood, characterised and stored. After excluding infants who have already suffered severe preterm brain injury, based on cranial ultrasounds in first week of life, preterm infants will be infused with autologous UCBCs via the intravenous route at a dose of 25–50 million UCBCs/kg body weight of live cells, with the cell number being the maximum available up to 50 million cells/kg. A minimum of 20 infants will be administered autologous UCBCs. Primary outcomes will include feasibility and safety. Feasibility will be determined by access to sufficient cord blood at collection and UCBCs following processing. Safety will be determined by lack of adverse events directly related to autologous UCBC administration in the first few days after cell administration. Secondary outcomes studied will include neonatal and neurodevelopmental morbidities till 2 years of life. Additional outcomes will include cell characteristics of all collected cord blood, and cytokine responses to cell administration in transplanted infants till 36 weeks' corrected age. Ethics and dissemination: Monash Health Human Research Ethics Committee approved this study in December 2019. Recruitment is to commence in July 2020 and is expected to take around 12 months. The findings of this study will be disseminated via peer-reviewed journals and at conferences. Trial registration number: ACTRN12619001637134.